Social aspects of the contract - Шуст, Наталія Борисівна; Барікова, Анна Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article is devoted to the analysis of the motivation conception of the treaty concluding according tothe example of the energy and other resources supply connected via a network.